Liver transplantation for polycystic disease: A cumbersome benign disease. (March 2023) - Calleri, A.; Lavezzo, B.; Biancone, L.; Romagnoli, R.; Martini, S.
Abstract : Background: Liver transplantation (LT) or simultaneous liver-kidney transplantation (SLKT) remain the curative treatment for liver (PCLD) and liver-kidney (PCLKD) polycystic disease. We aimed at describing pre- and post-transplant characteristics of polycystic patients undergoing LT/SLKT. Methods: Patients who underwent LT/SLKT for polycystosis in our Centre from 01/01/2010 to 30/06/2022 were enrolled. Follow-up ended on 30/11/2022. Results: among 1754 LTs, 63(3.6%) were performed for polycystosis (45/63 SLKT). 48/63(76.2%) female; median age 52 years[IQR 48-56]; median BMI 23.7 kg/m 2 [22.6-26.0]. Median serum creatinine 5.7 mg/dL[4.1-7.8], eGFR 12.2 mL/min[7.8-17.7] for SLKT patients (60.4% on pre-LT dialysis). Nine patients had pre-transplant cyst interventions. 58/63(92.1%) underwent LT due to abdominal fullness with sarcopenia (median liver weight 3950g[2450-6750]; median largest cyst size 7.0 cm[5.0-9.2]); 19/63(30.2%) showed refractory ascites. 10/63(15.9%) were pre-LT colonized by multidrug-resistant bacteria. During transplant: 6(9.5%) patients underwent venous-venous bypass and 9(14.2%) temporary porto-cava shunt; 18/63 (28.6%) piggy-back technique. Median liver cold ischemia time was 447 min[369-504]; median number of red blood cell transfusion was 7[3-16]. Among 48 patients listed for SLKT, 7/48(14.6%) underwent a delayed kidney transplantation from the same liver donor and 3/48(6.3%) due to the complexity of LT surgery, were then listed for sequential kidney transplant. After transplant: 41/69(65.1%) were extubated within 48-hours; median ICU-stay was 5 days[3-9] and hospital length-of-stay 17 days[12-25]. Two patients underwent re-LT for primary non-function and 28/63(44.4%) post-transplant surgical revisions. After a median follow-up of 4.1 years [1.6-7.7]: 59/63(93.7%) were alive; 3 patients died for sepsis 3 weeks after transplant and 1 patient for HHV8-induced hemophagocytic syndrome 3 years later. Conclusions: PCLD/PCLKD is a cumbersome and insidious benign disease. 16% of our patients were pre-transplant colonized by multidrug-resistant bacteria and post-transplant early surgical revisions were needed in 44% of the patients. However, the expertise of a high-volume transplant Centre allowed to achieve a 3-year survival rate of 93.7%.